Fabrication of carbon nano-tubes decorated with ultra fine superparamagnetic nano-particles under continuous flow conditions - Chin, S.F.; K., Swaminathan Iyer; Raston, Collin L. (Royal Society of Chemistry, 2008)
Ultra fine (2–3 nm) magnetite (Fe3O4) nano-particles are uniformly deposited on single-walled carbon nano-tubes (SWCNTs) pre-functionalised with carboxylic acid groups using microwave radiation. The deposition process involves chemical precipitation associated with continuous flow spinning disc processing (SDP), as a rapid, environmentally friendly approach which is readily scalable for large scale synthesis. The resulting decorated SWCNTs are superparamagnetic with specific saturated magnetization of 30 emu g−1.